2022
DOI: 10.3389/fendo.2022.913370
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expressions of Transfer RNA-Derived Small RNAs and microRNAs in the Vitreous Humor of Proliferative Diabetic Retinopathy

Abstract: PurposeWe sought to reveal the expression profiles of transfer RNA-derived small RNAs (tsRNAs) and microRNAs (miRNAs) in the vitreous humor of patients with proliferative diabetic retinopathy (PDR).MethodsVitreous humor samples were obtained from PDR patients and a control group for this study. Sequencing of small RNAs was conducted to assess the expression profiles of tsRNAs and miRNAs in both groups, which was followed by validation using reverse transcription-quantitative real-time polymerase chain reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The alignment of piRNAs with other ncRNAs revealed their potential crosstalk in the regulation of development, stress and circadian rhythm. Several studies have shown the correlation between stress and differentially expressed tsRNAs with the pathological implications observed during the course of a disease condition, including DR. 88,89 In line with this, hypoxic stress may alter the expression of the 3rd motif containing td-piRNAs, which in turn can regulate the ocular pathogenesis during DR and other related disorders. On the other hand, the presence of sd-piRNAs could be of importance during the developmental stage of the retina, which needs to be validated through functional experiments.…”
Section: Discussionmentioning
confidence: 86%
“…The alignment of piRNAs with other ncRNAs revealed their potential crosstalk in the regulation of development, stress and circadian rhythm. Several studies have shown the correlation between stress and differentially expressed tsRNAs with the pathological implications observed during the course of a disease condition, including DR. 88,89 In line with this, hypoxic stress may alter the expression of the 3rd motif containing td-piRNAs, which in turn can regulate the ocular pathogenesis during DR and other related disorders. On the other hand, the presence of sd-piRNAs could be of importance during the developmental stage of the retina, which needs to be validated through functional experiments.…”
Section: Discussionmentioning
confidence: 86%
“…In contrast, Gomaa et al showed that miR-200b was elevated in PDR but it did not correlate with vitreous levels of VEGF (47). Yang et al identified seven miRNA that were elevated in PDR, and KEGG analysis showed that the target genes of these miRNA were most enriched in the Th17 cell differentiation pathway (48). Notably, interleukin-17, which is produced by Th17 cells, has been shown to promote retinal neovascularization through multiple mechanisms (4951).…”
Section: Main Textmentioning
confidence: 99%
“…In addition, it was revealed in the study performed on rats with induced diabetes that miRNA-200b in DR diseases is lower than in the healthy group [123]. According to the vitreous humor, there were studies suggesting changes in several particle concentrations in PDR groups: miRNA-125, miRNA-21, hsa-miRNA-6734-5p, and hsa-miRNA-1297 [124,125]. MiRNAs, such as hsa-miRNA-3184-3p, hsa-miRNA-24-3p, and hsa-miRNA-197-3p, were assessed to be upregulated in the vitreous humor of PDR patients; furthermore, anti-VEGFfactor administration led to lower expression of those particles [124].…”
Section: Micrornasmentioning
confidence: 99%
“…According to the vitreous humor, there were studies suggesting changes in several particle concentrations in PDR groups: miRNA-125, miRNA-21, hsa-miRNA-6734-5p, and hsa-miRNA-1297 [124,125]. MiRNAs, such as hsa-miRNA-3184-3p, hsa-miRNA-24-3p, and hsa-miRNA-197-3p, were assessed to be upregulated in the vitreous humor of PDR patients; furthermore, anti-VEGFfactor administration led to lower expression of those particles [124]. However, vitreous humor parameter measurements are not easy to perform.…”
Section: Micrornasmentioning
confidence: 99%